Development And Characterization Of Gastroretentive Floating Drug Famotidine - Thareja, Rakhi; Tiwari, Yogesh; Kothari, Lokesh Premchand; Somasundaram, Jeevanandham; Srivastav, Yash; Borkar, Dinesh Prabhakar; Chouhan, Ajay; Kumar, Ritesh (Journal of Neonatal Surgery, 2025)
In this study, gastroretentive famotidine microballoons were designed and studied with the purpose of improving the treatment of peptic ulcers by extending the duration of stomach retention and regulating the release of the medicine. With a systematic modification in polymer-drug ratios ranging from 1:1 to 1:3, and stirring speeds ranging from 900 to 1500 revolutions per minute, nine different formulations (F1-F9) were created with HPMC K4M through the process of emulsion solvent diffusion. Excellent micromeritic qualities were demonstrated by the microballoons, as evidenced by appropriate flow characteristics (angle of repose: 22.14°-27.19%; Carr's index: 7.93-13.11%) and sustained buoyancy (>12 hours, 64.17-83.21%), all of which are essential for stomach retention. In order to ensure efficient drug loading, a high drug encapsulation efficiency (63.47-70.34%) was utilised. While FTIR and DSC tests demonstrated that there were no interactions between the medication and the excipient, scanning electron microscopy (SEM) revealed porous spherical structures that made flotation easier. In vitro release experiments demonstrated that the kinetics of the formulation were dependent on the formulation. The formulations F1, F4-F5, and F7-F9 adhered to the Korsmeyer-Peppas model, while F2 and F6 adhered to the Higuchi kinetics. F3 displayed optimal zero-order release (R2=0.9954). Through the maintenance of prolonged therapeutic drug levels in the stomach, this gastroretentive system is able to successfully address the pharmacokinetic limitations of famotidine, particularly its short elimination half-life (2.5-4 hours). Famotidine's therapeutic potential for acid-related illnesses is considerably enhanced by the combination of extended buoyancy and controlled release profile. This combination has the potential to improve treatment efficacy while simultaneously reducing the frequency of dose to minimise adverse effects. Based on these data, it appears that microballoons based on HPMC K4M could be a promising method for the targeted delivery of famotidine to the stomach